Hospital Management Strategies in Improving the Quality of Inpatient Services - Suaib Suaib; Victor E.D Palapessy; Rini Susanti; Rusli Abdullah; Djunaedi Djunaedi; Restu Prihandini Widiar (International Journal of Health Sciences, 2026)
ABSTRACT The quality of healthcare services is an important indicator in assessing hospital performance. Quality inpatient services can improve patient satisfaction and public trust in healthcare facilities. Hospital management has a strategic role in designing and implementing various policies to improve service quality. This study aims to analyze hospital management strategies in improving the quality of inpatient services. The study used a descriptive analytical design with a cross-sectional approach . The study sample was 90 inpatients selected using a purposive sampling technique. Data were collected through patient satisfaction questionnaires and service observations. Data analysis used the chi-square test . The results showed that the implementation of good management strategies such as improving the competence of healthcare workers, improving facilities, and an effective service management system had a significant relationship with improving the quality of inpatient services (p = 0.017). It was concluded that hospital management strategies have an important influence in improving the quality of inpatient services. Keywords: Hospital Management, Service Quality, Inpatient Care, Patient Satisfaction